FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNA TRANSPORTASI GOJEK DI KOTA SEMARANG: SEBUAH ANALISIS KUALITATIF - Totok Wibisono; Nuria Universari; Adijati Utaminingsih (Jurnal Dinamika Sosial Budaya, 2017)
Taxi is one of the most popular means of transportation. The development of digital technology today makes booking taxi easier online. In Semarang City, Gojek is one of the first online-based transport providers to attend. Competition in the online transport business is getting tighter with the presence of Grab and Uber. The increasingly intense competition in the online transportation business makes the research team interested to examine the factors that affect the users of online-based transport services choose using Gojek with Go-Car service. The research was conducted qualitatively. Informants in this study are online transportation users and drivers in the city of Semarang who have been using and become a driver of Go-Car for more than six months. Data collection techniques use in-depth interviews, documentation and literature review. Data analysis methods used in this study using data reduction, triangulation and drawing conclusions The results showed that the factors that affect consumers to use Go-Car services can be grouped into four. The four factors are price (efficient), convenience (security, simplicity, practicality), profit (sales promotion) and psychological factor (motivation).